Dynamics Process of Geomorphology at North Coast of Java between the river and the river Pemali Cisanggarung Brebes Central Java - Priyono, Kuswaji Dwi (Forum Geografi, 1998)
This research was carried out in the Coastal Area of North Java, District Brebes, Central Java. It aims at finding the mechanism of factor that influence the dinamics of coastal geomorphological process and the distribution of the dynamics of the geomorphological process. The primary data consist of coastal forms, coastal building/ human activity, sea current, and distribution of the coastal sediment were collected by field observation and measurement. The secondary data consists of the climate, wave, bathimetry, tide, and regional sea current were collected from the related institutions. The technique of data analysis includes Beaufort Scale is employed to find out the characteristics of wind and wave. The laboratory analysis is used to find out the distribution of the coastal sediment. The discriptive analysis is used to desribe the sea current, tide, bathimetry, and human activity.The outcome of this research indicates that Mousoon wind making waves and longshore current can transport sediments which come from Cisanggarung and Pemali river. The small range tide (95 cm), the fine coastal sediment (clay), the shallow bathimetry (0 â 5 m), and human activity (building coastal pand) to provoke the dynamical changing of coasline. The dynamics of the geomorphologycal process from 1944 to 1964 indicates that the coastal area progressed dynamicly; from 1964 â 1997 indicates that the some coastlines (location 1, 4, 5, and 6) progressed, some coastline (location 2, 3, 7, and 8) regressed, and some coastlines (between location 3 to 4 and location 6 to 7) were relativelly stable.